Genetic Polymorphisms Associated to Folate Transport as Predictors of Increased Risk for Acute Lymphoblastic Leukemia in Mexican Children - Zaruma-Torres, Fausto; Lares-Asseff, Ismael; Lima, Aurea; Reyes-Espinoza, Aarón; Loera-Castañeda, Verónica; Sosa-Macías, Martha; Galaviz-Hernández, Carlos; Arias-Peláez, María C.; Reyes-López, Miguel A.; Quiñones, Luis A. (Frontiers in Pharmacology, 2016)
Acute lymphoblastic leukemia (ALL) is a frequent neoplasia occurring in children. The most commonly used drug for the treatment of ALL is methotrexate (MTX), an anti-folate agent. Previous studies suggest that folate transporters play a role in ALL prognosis and that genetic polymorphism of genes encoding folate transporters may increase the risk of ALL. Therefore, the main goal of this study was to determine the associations among six genetic polymorphisms in four genes related with the folate transporter pathway to determine a relationship with the occurrence of ALL in Mexican children. A case-control study was performed in 73 ALL children and 133 healthy children from Northern and Northwestern Mexico. COL18A1 (rs2274808), SLC19A1 (rs2838956), ABCB1 (rs1045642 and rs1128503) and ABCC5 (rs9838667 and rs3792585). polymorphisms were assayed through qPCR. Our results showed an increased ALL risk in children carrying CT genotype (OR=2.55, CI 95% 1.11-5.83, p=0.0001) and TT genotype (OR=21.05, CI 95% 5.62-78.87, p<0.0001) of COL18A1 rs2274808; in SLC19A1 rs2838956 AG carriers (OR=44.69, CI 95% 10.42-191.63, p=0.0001); in ABCB1 rs1045642 TT carriers (OR=13.76, CI 95% 5.94-31.88, p=0.0001); in ABCC5 rs9838667 AC carriers (OR=2.61, CI 95% 1.05-6.48, p<0.05); and in ABCC5 rs3792585 CC carriers (OR=9.99, CI 95% 3.19-31.28, p=0.004). Moreover, several combinations of genetic polymorphisms were found to be significantly associated with a risk for ALL. Finally, two combinations of ABCC5 polymorphisms resulted in protection from this neoplasia. In conclusion, certain genetic polymorphisms related to the folate transport pathway, particularly COL18A1 rs2274808, SLC19A1 rs2838956, ABCB1 rs1045642 and ABCC5 rs3792585, were associated with an increased risk for ALL in Mexican children.